2003
DOI: 10.1074/jbc.m308562200
|View full text |Cite
|
Sign up to set email alerts
|

PIAS1-mediated Sumoylation of Focal Adhesion Kinase Activates Its Autophosphorylationn

Abstract: Focal adhesion kinase (FAK) is a protein tyrosine kinase enriched in focal adhesions, which plays a critical role in integrin-dependent cell motility and survival. The crucial step in its activation is autophosphorylation on Tyr-397, which promotes the recruitment of several enzymes including Src family kinases and the activation of multiple signaling pathways. We found in a yeast two-hybrid screen that the N-terminal domain of FAK interacted with protein inhibitor of activated STAT1 (PIAS1). This interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 62 publications
(61 reference statements)
7
81
0
3
Order By: Relevance
“…The machinery necessary for protein sumoylation is mostly nuclear (Melchior et al, 2003), although an increasing number of sumoylated proteins act outside the nucleus. These include cytosolic proteins such as a-catenin, SCG10, phosducin (Gocke et al, 2005;Klenk et al, 2006), and the membrane spanning or attached proteins GLUT1 and GLUT4 transporters (Giorgino et al, 2000), or the focal adhesion kinase (Kadaré et al, 2003). It is therefore possible that these proteins are subject to nucleocytoplasmic cycling that facilitates their sumoylation in the nucleus and the subsequent redistribution to the cytosol and/or cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The machinery necessary for protein sumoylation is mostly nuclear (Melchior et al, 2003), although an increasing number of sumoylated proteins act outside the nucleus. These include cytosolic proteins such as a-catenin, SCG10, phosducin (Gocke et al, 2005;Klenk et al, 2006), and the membrane spanning or attached proteins GLUT1 and GLUT4 transporters (Giorgino et al, 2000), or the focal adhesion kinase (Kadaré et al, 2003). It is therefore possible that these proteins are subject to nucleocytoplasmic cycling that facilitates their sumoylation in the nucleus and the subsequent redistribution to the cytosol and/or cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…26 Previous work has indicated that phosphorylation and SUMOylation can interact within the same protein to alter prevalence of the other modification. Examples of this include focal adhesion kinase where SUMOylation promotes autophosphorylation, 40 heat-shock factors 1 and 4b, myocyte enhancer factor 2, GluK2 kainate receptor, or estrogen receptor b that require phosphorylation for secondary SUMOylation, 41-45 DNA binding protein SATB1 where phosphorylation prevents SUMOylation, 46 and microtubule stabilizing Tau protein where either phosphorylation or SUMOylation promotes the other modification. 47 In the case of CRMP2, Fyn phosphorylation reduces SUMOylation, consequently reducing CRMP2s interaction with NaV1.7.…”
Section: Resultsmentioning
confidence: 99%
“…Using FAK, a non-receptor tyrosine kinase, as a specific example of tyrosine kinases, we demonstrated that SUMOylation reduction decreased the activity of FAK. The kinase activity of FAK is dependent on its autophosphorylation on Tyr-397, which, in turn, is positively modulated by SUMOylation (13). We examined whether GA treatment could alter FAK autophosphorylation at Tyr-397 (as a readout of the activation of FAK).…”
Section: System-wide Cross-talk Between Protein Sumoylation Andmentioning
confidence: 99%